A Circumplex Model of Couple Configurations in Relational Trauma Context: An Example of Practice‐Based Model Development. (13th July 2018) - Butler, Mark H.; Spencer, Travis J.
Abstract : We propose a circumplex model and typology of patterns of couple engagement to help therapists assess and shape positive couple engagement, prerequisite to successful resolution of relational trauma. View or value of self in relation to other (VSIRO) is conceived as a primary engine organizing couple relationships and patterns of engagement. VSIRO is conceptualized along a continuum anchored at opposite poles by inflated (self‐aggrandizing) versus collapsed (self‐negating) VSIRO, with a balanced (egalitarian) VSIRO as the target position, consisting of self and other mutuality, respect, and equality. Two axes (one for each partner) form the circumplex model of five couple configurations—four quadrants plus a balanced, mid‐axes region. Using couple configuration conceptualization to address patterns of engagement is an essential prerequisite to resolving couple relational trauma.